2016
DOI: 10.1002/cite.201600071
|View full text |Cite
|
Sign up to set email alerts
|

Physikalische Verfahren zur Entalkoholisierung verschiedener Getränkematrizes und deren Einfluss auf qualitätsrelevante Merkmale

Abstract: Membranbasierte und thermische Verfahren werden seit vielen Jahren zur Herstellung alkoholfreier Getränke genutzt, um Ethanol aus Bier oder anderen alkoholhaltigen, fermentierten Matrizes zu entfernen. Ziel ist, Ethanol möglichst selektiv und unter Berücksichtigung der Verluste wertgebender Aromastoffe zu entziehen. Neben gesetzlichen Grundlagen und gesundheitsrelevanten Aspekten werden verschiedene Technologien sowie deren Auswirkungen auf die Aromastoffzusammensetzung von Zwischen-und Endprodukten erläutert.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Here, such participants also rated a NAB as generally sweeter. These findings seem logical since rational and responsible emotions are commonly associated with NAB consumption [ 10 ], and NAB is often considered sweeter than its alcoholic counterpart [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, such participants also rated a NAB as generally sweeter. These findings seem logical since rational and responsible emotions are commonly associated with NAB consumption [ 10 ], and NAB is often considered sweeter than its alcoholic counterpart [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beverages produced by restricted fermentation or complete elimination of the fermentation process often exhibit an unpleasant taste of sweet wort due to the fact that yeast cannot sufficiently reduce the high aldehyde concentration in the wort at given operating conditions (Montanari et al 2009). Other process alternatives such as dealcoholisation by gas desorption (Hertel 2011), extraction with supercritical CO 2 or adsorption with silica gels have been developed but are of no industrial relevance (Müller et al 2016).…”
Section: Origin Of Aldehyde Formation During Regular and Alcohol-freementioning
confidence: 99%
“…The following paragraphs will thus rather focus on scouting technologies for the direct removal of aldehydes. When targeting the aldehyde off-flavours, the challenge lies in choosing for a high selectivity over other beer constituents thus preserving the natural nutritional value and taste of an AFB (Müller et al 2016). Figure 5 shows possible mechanisms to accomplish a selective removal of aldehydes from AFBs.…”
Section: Impact Of Alcohol-free Beer Composition On the Perception Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…logP is the 10-base logarithmic measure of the partition coefficient; log S or intrinsic solubility is the 10-base logarithmic measure of the solubility (mol/L) Food Eng Rev [4,5,21,33,35,38,45,63,66,68,89,93,94,99]. Few recent research works unequivocally demonstrated the application of Membrane Distillation (MD) and Vacuum Membrane Distillation (VMD) for flavor recovery during the last 4 years [1,21,68,77]. Performance of MD is investigated during beer dealcoholization processing and the effect of feed and vacuum pressure are investigated on flux and selectivity of a thin-film composite polyamide membrane.…”
Section: Aroma Recovery Through Distillationmentioning
confidence: 99%